Nilai-nilai Sosial dalam Al-Qur'an dan Implikasinya terhadap Pendidikan Karakter di Madrasah Ibtidaiyah - Dede Dwi Kurniasih; Anggreni Bako; Zaki Arrazaq; Yalizar Rahayu Sitorus; Hujjatul Fakhrurridha (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article discusses social values ​​in the Qur'an and their implications for character education in Madrasah Ibtidaiyah. In the context of Islamic education, the Qur'an provides various values ​​that serve as a foundation in the formation of students' character. Through an analysis of the Al-Hujurat surah, especially verses 11-13, this study found that values ​​such as monotheism, morals, social responsibility, compassion, brotherhood, justice, and mutual respect are highly emphasized. These values ​​play an important role in shaping the character of students in madrasahs, which not only focus on academic aspects but also on moral and social development. This study identifies values ​​such as monotheism, morals, social responsibility, compassion, and tolerance as key elements in character education that can help students face moral challenges in modern society. Through a qualitative descriptive approach and literature review, this article analyzes how these values ​​can be internalized in the education curriculum in madrasahs. The results show that the application of Qur'anic values ​​not only improves students' intellectual intelligence but also strengthens their moral and social dimensions. Thus, character education based on the Qur'an has the potential to create a generation that is not only knowledgeable but also has noble morals and a commitment to goodness.